Federal Income Tax Management - Vervil Mitchell; Josephine Turner; Michael S. Gutter; Nayda I. Torres; Horacio Soberon; Zeynep Copur (EDIS)
Revised! FCS-7026, an 8-page fact sheet revised by Josephine Turner, Michael S. Gutter, Nayda I. Torres, Horacio Soberon, and Zeynep Copur, has been updated for the current tax season. It describes the advantages of filing a federal tax return, who must file a return, itemizing deductions, computing income tax rates, credits, payments, preparing and filing your return, recordkeeping, and where to get help. Includes references. Published by the UF Department of Family Youth and Community Sciences, March 2009.